Publishing in the Academy of Management Journals - Rockmann, Kevin; Bunderson, Stuart J.; Leana, Carrie R.; Hibbert, Paul; Tihanyi, Laszlo; Phan, Phillip H.; Thatcher, Sherry M. B. (Academy of Management Review, 2021)
Perhaps you are a doctoral student, mapping out how to parcel your dissertation; perhaps you are a junior scholar, strategizing your research plan; perhaps you are a senior scholar, who is thinking about what you want to say to the field. No matter what stage you are at as a management researcher, you might be looking to the Academy of Management (AOM) journals as a natural home for any and all of these creative research pursuits. However, it might not always be crystal clear how you should craft your work for the AOM journals, what contribution you might make at each journal, and consequently to which journal you should target your intellectual contributions.